The culture trauma reflected in Kanafani's novel Return to Haifa within the genre of Palestinian resistance novels - Ye, Xinyu; Toklubok, Pabiyah (Global Academic Excellence, 2024)
This study examined the portrayal of cultural trauma in Ghassan Kanafani's novel "Return to Haifa" through character analysis. The aim of this study was to investigate the extent to which the characters portrayed in the novel serve as a reflection of the cultural trauma that was endured during and in the aftermath of the Nakba, a catastrophic event that occurred in 1948. The investigation utilized Jeffrey C. Alexander's conceptualization of cultural trauma as a theoretical lens for examination. This study employed a textual analysis approach to examine the effects of trauma on the primary characters, Said and Dov, and their subsequent development of a collective identity. The analysis of data focused on the evolution of self-awareness throughout the narrative, revealing the impact of trauma on individual and collective identity. The findings suggested that the memories and experiences of Palestine diasporas like Said, who were forced to leave their homeland, contribute to their cultural trauma and shape their sense of identity; also illuminated the importance of the Nakba as a crucial occurrence in the history of Palestine and the lasting impacts it has on the communal awareness of Palestinians. The study contributes to the understanding of how literature represents and addresses cultural trauma and its implications for the Palestinian community.